Apparent digestibility of fish waste oil in diets for laying hens - Brelaz , Kely Cristina Bastos Teixeira Ramos (2023)
This study aimed to assess the impact of incorporating fish waste oil into laying hens' diets on apparent nutrient digestibility and apparent metabolizable energy. A total of 72 Hisex White laying hens (25 weeks old) were employed in a completely randomized design, with treatments consisting of a control diet and an experimental diet (containing 3.5% fish oil), each with six replicates of six birds. The collected data underwent polynomial regression analysis at a 5% significance level. No significant differences (p > 0.05) were observed in the digestibility of dry matter, crude protein, mineral matter, crude fiber, and non-nitrogenous extract between the reference diet and the experimental diet containing fish waste oil. However, there were significant differences (p < 0.05) in the digestibility of ethereal extract (fat). Despite this, values for apparent metabolizable energy and apparent metabolizable energy corrected by nitrogen balance did not exhibit significant differences (p > 0.05) between the reference and experimental diets. In conclusion, the incorporation of 3.5% fish waste oil in laying hens' diets led to satisfactory nutrient digestibility and enhanced fat digestibility. Importantly, this inclusion did not adversely impact energy metabolism.